Human papillomavirus (HPV) knowledge and prevention practices among Sierra Sur, Oaxaca college students - Bustamante Ramos, Gisela Mayra (2015)
Introduction. Human papillomavirus (HPV) causes the world’s most important sexually transmitted infection and is considered the main agent for cervical cancer. Youngsters are most vulnerable as they usually begin sexual relations without protection. Objectives. To describe students’ knowledge of human papillomavirus infection prevention at Sierra Sur, Oaxaca University. Design. Quantitative, descriptive cross-sectional study. Place. Sierra Sur, Oaxaca, Mexico. Participants. University students from different programs who reported to have an active sexual life. Interventions. A closed response questionnaire was constructed and applied to the students by self-administration. Main outcome measures. The  instrument was divided into sections including sociodemographic, academic and sexual aspects, knowledge about HPV and prevention practices. Results. Male participants became sexually active earlier than women (x2 = 25.7, p = 0.048), had more partners (x2 = 34.09, p = 0.002), and about half of them did not use condom during sex. They were unaware that the virus is associated with cervical cancer (x2 = 17.5, p <0.001) and may cause cancer in men (x2 = 0.09, p = 0.760). They did not know the main clinical manifestations of the disease (x2 = 1.7, p = 0.415). Students of the health sciences had some knowledge on HPV diagnosis. Age did not affect knowledge on the virus. Conclusions. This study revealed that most students do not know the clinical features, management and treatment of the HPV infection and as a consequence are unaware of the importance of the transmission. It is necessary to give more importance to the sex education of university students and to raise awareness of the impact of the HPV infection, by informing about the transmission mechanisms, prevention methods, and clinical manifestations.